2016
DOI: 10.1016/j.amepre.2016.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Identifying and Tracking Gas Suicides in the U.S. Using the National Violent Death Reporting System, 2005–2012

Abstract: Public health policies to reduce a suicidal person's access to more lethal suicide methods require a reliable source of surveillance data on specific methods used in suicide. Small changes to NVDRS could make it an efficient and nimble surveillance system for tracking these deaths.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 37 publications
5
21
0
Order By: Relevance
“…The proportion of suicide deaths by inhalational asphyxia is similar to what has been observed in England and Wales as well as the U.S. (Azrael et al, 2016;Cantrell and Lucas, 2014) and the pattern of an increase in suicide by helium accompanied by a reduction by motor vehicle exhaust is also consistent with prior research (Azrael et al, 2016) although these changes likely represent two different co-occurring phenomena (i.e. social contagion of the helium method vs. an increase in the proportion of motor vehicles fitted with catalytic converters (Studdert et al, 2010), respectively).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The proportion of suicide deaths by inhalational asphyxia is similar to what has been observed in England and Wales as well as the U.S. (Azrael et al, 2016;Cantrell and Lucas, 2014) and the pattern of an increase in suicide by helium accompanied by a reduction by motor vehicle exhaust is also consistent with prior research (Azrael et al, 2016) although these changes likely represent two different co-occurring phenomena (i.e. social contagion of the helium method vs. an increase in the proportion of motor vehicles fitted with catalytic converters (Studdert et al, 2010), respectively).…”
Section: Discussionsupporting
confidence: 82%
“…The only Canadian study on the topic was a case series in British Columbia which identified 20 suicide deaths by helium asphyxia in the province from 1999(Ogden and Hassan, 2011. More recent, population-level analyses have demonstrated increases in suicide death by helium asphyxia in the U.S. (Azrael et al, 2016;Hassamal et al, 2015), the Netherlands (van den Hondel et al, 2016), Australia and Sweden (Austin et al, 2011), England and M A N U S C R I P T 6 Wales and Hong Kong (Chang et al, 2016) and have demonstrated a signal that the method may be spreading to Asia (Chang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be added that in the period from 1985 to 1999, no suicides due to helium inhalation were recorded in the territory of South Australia [14]. A review [15] of suicide cases in the USA in the years 2005-2012 showed that helium was used in 665 cases of a total of 80,715 suicides registered in the National Violent Death Reporting System (NVDRS). There were a total 3242 cases of suicidal deaths by gas asphyxiation, 73% of which were caused by carbon monoxide (CO), followed by helium (21%) [15].…”
Section: Introductionmentioning
confidence: 99%
“…A review [15] of suicide cases in the USA in the years 2005-2012 showed that helium was used in 665 cases of a total of 80,715 suicides registered in the National Violent Death Reporting System (NVDRS). There were a total 3242 cases of suicidal deaths by gas asphyxiation, 73% of which were caused by carbon monoxide (CO), followed by helium (21%) [15]. Similar results were obtained by a retrospective analysis of suicides in San Diego County between 2000 and 2012.…”
Section: Introductionmentioning
confidence: 99%